Assessment in Education Implications for Leadership - Scott, Shelleyann; Scott, Donald E.; Webber, Charles F. (The Enabling Power of Assessment, 2016)
This book provides key insights into how educational leaders can successfully navigate the turbulence of political debate surrounding leading student assessment and professionalised practice. Given the highly politicised nature of assessment, it addresses leaders and aspiring leaders who are open to being challenged, willing to explore controversy, and capable of engaging in informed critical discourse. The book presents the macro concepts that these audiences must have to guide optimal assessment policy and practice. Collectively, the chapters highlight important assessment purposes and models, including intended and unintended effects of assessment in a globalised context. The book provides opportunities to explore cultural similarities and particularities. It invites readers to challenge taken-for-granted assumptions about ourselves and colleagues in other settings. The chapters highlight the cultural clashes that may occur when cross-cultural borrowing of assessment strategies, policies, and tools takes place. However, authors also encourage sophisticated critical analyses of potential lessons that may be drawn from other contexts and systems. Readers will encounter challenges from authors to deconstruct their assessment values, beliefs, and preconceptions. Indeed, one purpose of the book is to destabilise certainties about assessment that prevail and to embrace the assessment possibilities that can emerge from cognitive dissonance.